Management of common scab (Streptomyces scabies) of potato through eco-friendly approach - and S.M. CHAUDHARI, RAMAKANT GHARATE, NARENDRA SINGH* (Indian Phytopathology, 2016)
Common scab disease of potato caused by Streptomyces scabies, is an important disease which occurs throughout the potato growing regions of the world and is usually prevalent in neutral to slightly alkaline soil, especially during dry years. The field experiment was conducted during rabi seasons of 2011-13 in naturally infested field with scab pathogen at Potato Research Station, S.D. Agricultural University, Deesa (Gujarat) using bio-agents, boric acid and organic amendments (manure and cake) for effective management of common scab pathogen. Among different bio-agents (Trichoderma asperellium, Bacillus subtilis and Pseudomonas fluorescens) and safer chemical tested against the disease, the tuber treatment with 3 per cent boric acid spray before planting recorded the lowest disease incidence (48.0%) and disease index (1.46) with highest healthy (163.07 q/ha) and total tuber yield (339.30 q/ha). Tuber treatment with T. asperellium @ 10 g/kg recorded the disease incidence 54.00 per cent and index of 1.87 as compared to control (68.50% and 3.54) with minimum diseased tuber yield (188.74 q/ha). Among different organic amendments tested, soil application of mustard cake @ 2 t/ha registered minimum disease incidence (38.33%) and disease index (0.72) followed by neem cake @ 2 t/ha. Though, soil application of vermicompost @ 2 t/ha gave highest tuber yield (332.4 q/ha).